Tree Transplantation - A Great Initiative for A Greener Development - Naik, M. Ramesh; Das, Shrestha; Sen, Sneha; Ramanjaneyulu, A. V.; Teja, R. Ravi; Lakshmi, D. Vijaya; Chaitanya, T.; Joseph, B. (Chronicle of Bioresource Management, 2025)
Tree transplantation is becoming an increasingly important tool in conservation, helping to reduce environmental damage caused by deforestation and urban expansion. The process involves key biological, mechanical, and logistical steps, including planning, root preparation, safe transport and post-care management till successful establishment. When executed properly, tree transplantation can save valuable time, preserve biodiversity, enhance urban green spaces and deliver immediate environmental benefits such as carbon sequestration and temperature regulation. However, the practice also presents challenges, including high costs, technical complexity, and variable success rates depending on tree species and site conditions. Real-world examples demonstrate that successful transplantation is achievable with appropriate planning, specialized tools and coordinated efforts across disciplines. Emphasizing the importance of standardized guidelines and stronger policy support, tree transplantation can become a valuable component of sustainable urban development strategies.